HUBUNGAN PENDIDIKAN DAN PELATIHAN DENGAN KINERJA PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN SELUMA - -, Wagini (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2014)
Wagini; TheRelationshipof Educationand Training Toward EmployeePerformance in Religion Ministry in Seluma District. Purpose of this study is todetermine the relationship ofeducationandtrainingon employee performancein religion ministry in Seluma Regency. The populationin this study is all existing employeewithin the office of Religion Ministry inSeluma District. The sampling technique used in this study isa purposive sampling method. Based on the criteria set of samples so the sample is taken from 50 people. The result shows a good indicator of education and training as well as the performance obtained good grades,means by getting employees follow the training will be followed by increasing in performance, because in general training followed by civil servantsat the Religion Ministry in Seluma Districtisa training to in crease knowled geandinsight about jobs and regulations relating to the dutiesand functions of each principal.Kata kunci: Pendidikan dan Pelatihan, Kinerja Pegawai